Meningkatkan Place Attachment: Mengungkap Pengaruh Urban Park Value, Flow Experience, Eudaimonic Satisfaction, dan Hedonic Satisfaction - Wardani, Cevi Tri Kusumah; Romi, Mochamad Vrans (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The aim of this research is to examine the influence of urban park value and flow experience on place attachment. This quantitative research uses a survey method with a total of 100 respondents. The data analysis technique is through multiple linear regression using SPSS version 25 and the online Sobel test. The results show that physical attributes have an indirect positive effect on place attachment through eudaimonic satisfaction; scenery has a direct positive effect on place attachment; and, flow experience has no effect on place attachment. The research results are useful for managers of the objects being assessed and similar green open space industries regarding designing relevant strategies to improve the quality of place attachments.